Unawareness of HCV serostatus among persons newly diagnosed with HIV - Paola Scognamiglio; Assunta Navarra; Nicoletta Orchi; Gabriella De Carli; Silvia Pittalis; Ilaria Mastrorosa; Ubaldo Visco Comandini; Chiara Agrati; Andrea Antinori; Vincenzo Puro; Giuseppe Ippolito; Enrico Girardi (Elsevier, 2019)
Treatment of chronic HCV infection with direct acting antivirals can achieve high rates of sustained viral response in persons with HIV. In the perspective of HCV elimination in this population, high rates of HCV detection will be needed. We evaluated the unawareness of HCV infection in 2927 persons newly diagnosed with HIV during 2004-2015 in Rome, Italy. Two-hundred-fifty persons (8.5%) were anti-HCV positive. The proportion of HCV-unaware individuals at the time of HIV diagnosis was 58.0% (145/250), without significant variations over time, 17.2% showed an advanced fibrosis stage. The absence of previous HIV testing was significantly associated with HCV unawareness. Keywords: Hepatitis, HCV, HIV-HCV coinfection, Late diagnosis, Italy